2018
DOI: 10.1186/s12985-018-1050-3
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine plus tenofovir combination therapy versus lamivudine monotherapy for HBV/HIV coinfection: a meta-analysis

Abstract: BackgroundCurrently, there is no consensus on the efficacy and safety of lamivudine (LAM) plus tenofovir disoproxil fumarate (TDF) combination therapy versus lamivudine monotherapy in HBV/HIV coinfected patients.MethodsA comprehensive literature search was performed in English and Chinese databases. Both relevant dichotomous and continuous variables were extracted, and the combined outcomes were expressed as a risk ratio (RR) or a standard mean difference (SMD).ResultsEleven eligible studies were included in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The causes of this heterogeneity should be identified, as long-term treatment resulted in higher rates of HBeAg loss and seroconversion. The combination of TDF + 3TC/FTC seemed to be more effective in patients with documented 3TC resistance (Luo et al, 2018). Differences in immune restoration after ART initiation were observed, with various rates of HBeAg seroclearance, as a sudden increase in CD4 + T-cell counts may promote a rapid immune response (Miailhes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of this heterogeneity should be identified, as long-term treatment resulted in higher rates of HBeAg loss and seroconversion. The combination of TDF + 3TC/FTC seemed to be more effective in patients with documented 3TC resistance (Luo et al, 2018). Differences in immune restoration after ART initiation were observed, with various rates of HBeAg seroclearance, as a sudden increase in CD4 + T-cell counts may promote a rapid immune response (Miailhes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This group of drugs has been routinely used in the treatment of viral infections for many years ( Luo et al, 2018 ; Keam, 2007 ; Rachlis, 1990 ; Jordan et al, 2018 ; Churchill et al, 2016 ; Organization, 2018 ). It is characterized by high affinity to viral enzymes and low affinity to human enzymes.…”
Section: Nucleotide and Nucleoside Analogsmentioning
confidence: 99%
“…However, another study reported no difference in effect between TDF monotherapy versus combined therapy of TDF and 3TC/FTC in managing chronic HBV infection among HBV monoinfected individuals (28). Among HIV/HBV coinfected individuals, a combination of 3TC and TDF is considered more efficacious compared to 3TC monotherapy among HIV/HBV coinfected individuals (29).…”
Section: Discussionmentioning
confidence: 99%